The Double Whammy of Obesity and Diabetes on Female Reproductive Health - Thong, Eleanor P.; Burden, Christy (Seminars in Reproductive Medicine, 2020)
The rising global prevalence of obesity and diabetes, especially in youth, confers substantial metabolic consequences and increased mortality in affected individuals. While obesity is strongly tied to the development of insulin resistance and type 2 diabetes, emerging evidence shows that obesity rates are also increasing exponentially in those with type 1 diabetes, contributing to insulin resistance and cardiometabolic sequelae. In addition, both obesity and diabetes can exert adverse effects on female reproductive health independently, with the presence of both conditions likely to exacerbate reproductive dysfunction in this cohort. If the current trends in obesity and diabetes incidence persist, it is likely that more women will be at risk of obesity- and diabetes-related reproductive disorders. This review aims to describe the epidemiology and mechanisms of obesity in women with diabetes, and summarize current literature regarding reproductive disorders in diabetes and weight management strategies in this cohort.
Keywords: obesity; diabetes; female reproduction; polycystic ovary syndrome